Exploring barriers to switching “on time” to second-line antiretroviral therapy among nurses in primary health care facilities, Ekurhuleni Health District, South Africa - Immaculate Sabelile Tenza; Christine Njuguna; Pumla Pamella Sodo; Aviva Ruch; Joel Msafiri Francis; Olufemi Babatunde Omole; Richard Cooke; Samuel Agbo; Laurel Baldwin-Ragaven (PLoS ONE, 2023)
Background Ensuring that all HIV-infected people receive antiretroviral therapy (ART) and achieve viral suppression are key South African strategies to end the AIDS epidemic in the country. National HIV treatment guidelines recommend an immediate switch to second-line ART following virological failure with first-line ART. Nurses based in district health facilities are at the forefront of implementing this recommendation. While there are often delays in switching and in some instances no switch, the reasons for and barriers to delayed switching are not well understood at the primary care level. Aim To explore the views of frontline nursing staff about factors contributing to delayed switching of patients who have failed first-line ART regimen in Ekurhuleni district, South Africa. Methods A qualitative study was conducted among 21 purposively sampled nurses who provide HIV treatment and care to patients in 12 primary health care (PHC) facilities in Ekurhuleni Health District, Gauteng Province, South Africa. Individual in-depth interviews explored nurses’ experiences regarding their recognition of virological failure and understanding of “on time” switching to second-line ART. Interviews probed the circumstances contributing to delays in switching. After digital audio recording and transcription, manual inductive thematic analysis was used to analyse the data. Findings Multiple barriers were identified: 1) Healthcare provider factors included a lack of knowledge and confidence coupled with demotivation in the workplace; 2) Patient issues similarly comprised a lack of knowledge as well as resistance to being switched to another drug regimen and loss to follow up; 3) Systems factors were poor facility leadership, shortages of medication, staffing constraints, and the inability to trace laboratory results, especially for migrant patients. Conclusion Reasons for delayed switching of patients to second-line ART are multifactorial and require integrated interventions at health provider, patient and health system levels.